Lignin-furfural biomass-based phenolic resin, preparation method and application thereof, plywood and preparation method thereof
By directly using lignin-branal-forming hybrid solution for bonus-reducing reasons, simplifying the preparation process of phenolic resin, solving the problem of insufficient complex processes and lignin phenolic hydroxyl content in existing technologies, and realized high-efficiency and environmentally friendly biomass. The preparation of basic phenolic resin improves the performance of adhesives.
Patent Information
- Application Number
- CN202411884194.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing biomass-based phenolic resin preparation technology is complex, and lignin needs to undergo pretreatment steps such as modification, phenolicization, dispersion and dispolymerization. Moreover, the phenolic hydroxyl content in lignin is insufficient, making it difficult to completely replace phenol, resulting in a decrease in the strength of the adhesive.
The phenolic resin is used to directly prepare the phenolic resin by lignin-branaltalty hybrid solution. By the bonus-concentration reaction of heat treatment and alkaline catalysts, improve the phenolic hydroxyl content in the wood quality, and simplify the process process.
The efficient preparation of lignin-pyramal biomass-based phenolic phenolic resin is achieved, and the phenolic hydroxyl content in lignin can be improved. It can replace phenol and formaldehyde raw materials 100%, enhance the adhesive strength of the adhesive and the life of the plywood.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phenolic resins, and in particular to a lignin-furfural biomass-based phenolic resin and a preparation method and application thereof, a plywood and a preparation method thereof. Background Art
[0002] Biomass is rich in hemicellulose and lignin. The products obtained by hydrolysis of hemicellulose contain aldehyde groups, and lignin contains phenolic hydroxyl groups. Using biomass containing aldehyde groups and phenolic hydroxyl groups as raw materials to completely or partially replace formaldehyde and phenol to synthesize biomass-based phenolic resins has been an urgent problem for scientists to solve in recent years. Most of the existing biomass-based phenolic resin preparation technologies use lignin to replace part of phenol, or use furfural to partially replace formaldehyde to synthesize biomass-based phenolic resins. After obtaining lignin from biomass raw materials, the existing preparation methods need to perform pretreatment steps such as modified phenolization, dispersion and depolymerization on the lignin, and then use it to prepare phenolic resins. The preparation steps of phenolic resins are complicated. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a lignin-furfural biomass-based phenolic resin and a preparation method and application thereof, plywood and a preparation method thereof. The lignin in the lignin-furfural mixed solution prepared by the present invention has a high content of phenolic hydroxyl groups in the lignin, and can be directly used to prepare phenolic resin without further modification, phenolization, dispersion and depolymerization, and the process is simple.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a lignin-furfural biomass-based phenolic resin, comprising the following steps: The biomass raw material, the organic solvent-water mixed solvent and the inorganic acid are mixed, the obtained acidic mixed solution is heat-treated under a protective atmosphere, the solid-liquid separation is performed, and the pH value of the obtained liquid component is adjusted to neutral to obtain a lignin-furfural mixed solution; the organic solvent in the organic solvent-water mixed solvent includes acetone; The lignin-furfural mixed solution and an alkaline catalyst are mixed, and the obtained lignin-furfural-catalyst mixed solution is subjected to an addition-polycondensation reaction to obtain a lignin-furfural biomass-based phenolic resin.
[0005] Preferably, the biomass raw materials include agricultural and forestry waste biomass and / or energy herbaceous plants; The inorganic acid includes sulfuric acid and / or phosphoric acid; The content of biomass raw materials in the acidic mixed liquid is 5-30wt%, and the content of inorganic acid is 1-50wt%; The volume fraction of water in the organic solvent-water mixed solvent is 10-50%.
[0006] Preferably, the heat treatment temperature is 140-180° C., the holding time is 5-10 min, and the pressure is 0.1-2 MPa.
[0007] Preferably, the mass ratio of lignin to furfural in the lignin-furfural-catalyst mixed solution is 0.8~1:0.6~0.8; when the mass ratio of lignin to furfural does not meet 0.8~1:0.6~0.8, additional lignin or furfural is added.
[0008] Preferably, the alkaline catalyst comprises one or more of alkali metal carbonate, alkali metal bicarbonate and ammonia; The mass of the alkaline catalyst accounts for 1-5% of the mass of the lignin-furfural mixed solution.
[0009] Preferably, the condensation reaction temperature is 80-120° C., and the time is 1-3 hours.
[0010] The present invention also provides a lignin-furfural biomass-based phenolic resin prepared by the preparation method described in the above technical solution.
[0011] The present invention also provides the use of the lignin-furfural biomass-based phenolic resin described in the above technical solution as an adhesive, wear-resistant material, waterproof material or insulating material.
[0012] The present invention also provides a plywood, characterized in that the adhesive used includes the lignin-furfural biomass-based phenolic resin described in the above technical solution.
[0013] The present invention also provides a method for preparing the plywood described in the above technical solution, comprising the following steps: applying adhesive to the slabs, laminating and hot pressing to obtain the plywood.
[0014] The present invention uses acetone as an extraction solvent and dispersant for lignin, which can effectively protect the lignin structure from being destroyed and prevent self-condensation. The extracted lignin is an acetone-soluble lignin component, and the prepared lignin has a higher content of phenolic hydroxyl groups. Compared with the conventional preparation method, the content of phenolic hydroxyl groups in lignin increases by 20-25%, which can 100% replace phenol, effectively improving the problem of reduced strength of phenolic resin adhesives caused by traditional alkali-soluble lignin replacing phenol. Moreover, the lignin-furfural mixed solution prepared by the present invention is used to prepare phenolic resin, and there is no need to disperse and depolymerize lignin, realizing the complete route design from raw materials to product synthesis of lignin-furfural biomass-based phenolic resin, improving the extraction and utilization efficiency of lignin and furfural and reducing the pretreatment steps, simplifying the process flow, saving energy consumption, improving economic benefits, and greatly reducing the production cost of phenolic resin.
[0015] The present invention adopts the lignin-furfural mixed solution as the raw material for preparing phenolic resin. The bonding strength of the prepared lignin-furfural biomass-based phenolic resin is higher than that of the lignin-furfural biomass-based phenolic resin prepared by dissolving lignin with a non-acetone solvent. The bonding strength of the lignin-furfural biomass-based phenolic resin at room temperature reaches 4.2±0.3MPa, and the adhesive performance is much higher than the national standard (≥0.7MPa, GB / T14732-2017). In the dry bonding strength test of the lignin-furfural biomass-based phenolic resin prepared by the present invention, all wood samples bonded with the lignin-furfural biomass-based phenolic resin showed 100% wood damage and good adhesive strength. Moreover, the lignin-furfural mixed solution prepared by the present invention can completely replace phenol and formaldehyde raw materials, has the characteristics of being green, non-toxic and environmentally friendly, and can greatly alleviate the pressure of oil resource shortage.
[0016] Furthermore, compared with the use of a strong base catalyst, the present invention uses weakly or moderately alkaline alkali metal carbonates and / or alkali metal bicarbonates and ammonia water as catalysts, which can reduce the damage to the structure of lignin caused by the alkali.
[0017] The plywood using the lignin-furfural biomass-based phenolic resin prepared by the present invention as an adhesive has high bonding strength between plywood layers, long service life, and is free of harmful substances such as formaldehyde, and has great advantages in furniture applications. DETAILED DESCRIPTION
[0018] The present invention provides a method for preparing a lignin-furfural biomass-based phenolic resin, comprising the following steps: The biomass raw material, the organic solvent-water mixed solvent and the inorganic acid are mixed, the obtained acidic mixed solution is heat-treated under a protective atmosphere, the solid-liquid separation is performed, and the pH value of the obtained liquid component is adjusted to neutral to obtain a lignin-furfural mixed solution; the organic solvent in the organic solvent-water mixed solvent includes acetone; The lignin-furfural mixed solution and an alkaline catalyst are mixed, and the obtained lignin-furfural-catalyst mixed solution is subjected to an addition-polycondensation reaction to obtain a lignin-furfural biomass-based phenolic resin.
[0019] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0020] The invention mixes biomass raw materials, an organic solvent-water mixed solvent and an inorganic acid, performs heat treatment on the obtained acidic mixed liquid under a protective atmosphere, separates the solid and the liquid, and adjusts the pH value of the obtained liquid component to neutral to obtain a lignin-furfural mixed solution; the organic solvent in the organic solvent-water mixed solvent includes acetone.
[0021] In the present invention, the biomass raw material preferably includes agricultural and forestry waste biomass and / or energy herbaceous plants; the agricultural and forestry waste biomass preferably includes one or more of corn stalks, corn cobs, bamboo powder, bagasse and wheat straw; the energy herbaceous plants preferably include energy grass, and the energy grass preferably includes switchgrass. In the present invention, the biomass raw material is preferably dried, crushed and sieved in sequence before use; the sieve size is preferably 20-80 mesh, and in a specific embodiment it can be 20 mesh, 30 mesh, 40 mesh, 50 mesh, 60 mesh, 70 mesh or 80 mesh, and the part under the sieve is used.
[0022] In the present invention, the content of biomass raw material (dry weight) in the acidic mixed solution is preferably 5-30wt%, and in specific embodiments it can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%.
[0023] In the present invention, the inorganic acid preferably includes sulfuric acid (H2SO4) and / or phosphoric acid (H3PO4); the content of the inorganic acid in the acidic mixed solution is 1~50wt%, and in specific embodiments it can be 1wt%, 4wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%.
[0024] In the present invention, the volume fraction of water in the organic solvent-water mixed solvent is preferably 10-50%, and in specific embodiments can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%.
[0025] The present invention has no particular limitation on the first mixing, as long as the raw materials can be mixed uniformly.
[0026] In the present invention, the protective atmosphere preferably includes nitrogen, argon or helium.
[0027] In the present invention, the temperature of the heat treatment is preferably 140-180°C, and in specific embodiments it can be 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C; the holding time of the heat treatment is preferably 5-10min, and in specific embodiments it can be 5min, 5.5min, 6min, 6.5min, 7min, 7.5min, 8min, 8.5min, 9min, 9.5min or 10min; the pressure of the heat treatment is preferably 0.1-2MPa, and in specific embodiments it can be 0.1MPa, 0.5MPa, 1MPa, 1.5MPa, 1.6MPa or 2MPa.
[0028] The present invention has no special limitation on the solid-liquid separation, and any solid-liquid separation method well known to those skilled in the art may be used, such as filtration, suction filtration or centrifugal separation; the residue obtained by the solid-liquid separation is cellulose, and the cellulose has high purity.
[0029] In the present invention, the alkali used for adjusting the pH value preferably includes one or more of sodium carbonate, potassium carbonate and ammonia water; the concentration of the ammonia water is preferably 25-28wt%, and in specific embodiments it can be 25wt%, 26wt%, 27wt% or 28wt%.
[0030] After the pH value is adjusted to neutral, the present invention preferably further comprises solid-liquid separation of the obtained neutral mixed solution, and concentrating the obtained liquid component to obtain a lignin-furfural-catalyst mixed solution. The present invention has no special limitation on the solid-liquid separation, and a solid-liquid separation method well known to those skilled in the art can be adopted, such as filtration, suction filtration or centrifugal separation. In the present invention, the concentration preferably comprises vacuum distillation; the purpose of the concentration is to recover the organic solvent. In the present invention, the volume fraction of water in the lignin-furfural-catalyst mixed solution is preferably 10-20%, and in specific embodiments it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%; if the water content in the lignin-furfural-catalyst mixed solution is too high, the rate of the subsequent addition-polycondensation reaction will be slowed down.
[0031] The present invention uses acetone as an extraction solvent and dispersant for lignin, which can effectively protect the lignin structure from being destroyed and prevent self-condensation. The extracted lignin is an acetone-soluble lignin component, and the prepared lignin has a higher content of phenolic hydroxyl groups, which has a good application prospect in the preparation of phenolic resin. Compared with the conventional preparation method, the phenolic hydroxyl content in lignin increases by 20-25%, and phenol can be 100% replaced. It can be directly used to prepare phenolic resin without modifying phenolization of lignin, and effectively improves the problem of reduced strength of phenolic resin adhesive caused by traditional alkali-soluble lignin replacing phenol. Moreover, the lignin-furfural mixed solution prepared by the present invention is used to prepare phenolic resin, and there is no need to disperse and depolymerize lignin, which realizes the complete route design from raw materials to product synthesis of lignin-furfural biomass-based phenolic resin, improves the extraction and utilization efficiency of lignin and furfural, reduces the pretreatment steps, simplifies the process flow, saves energy consumption, improves economic benefits, and greatly reduces the production cost of phenolic resin.
[0032] After obtaining the lignin-furfural mixed solution, the present invention mixes the lignin-furfural mixed solution with an alkaline catalyst, and performs an addition-polycondensation reaction on the lignin-furfural-catalyst mixed solution to obtain a lignin-furfural biomass-based phenolic resin.
[0033] In the present invention, the mass ratio of lignin to furfural in the lignin-furfural-catalyst mixture is preferably 0.8~1:0.6~0.8, and in specific embodiments, it can be 0.8:0.6, 0.8:0.7, 0.8:0.8, 0.9:0.6, 0.9:0.7, 0.9:0.8, 1:0.6, 1:0.7 or 1:0.8. In the present invention, when the mass ratio of lignin to furfural in the lignin-furfural-catalyst mixture does not meet the above ratio, it is preferred to add lignin or furfural; if the mass ratio of lignin to furfural in the lignin-furfural-catalyst mixture does not meet the above ratio and no lignin or furfural is added, the adhesive strength of the prepared lignin-furfural biomass-based phenolic resin is not affected, but the amount of the obtained lignin-furfural biomass-based phenolic resin will be reduced.
[0034] In the present invention, the alkaline catalyst preferably includes one or more of alkali metal carbonate, alkali metal bicarbonate and ammonia water; the alkali metal carbonate preferably includes potassium carbonate and / or sodium carbonate; the alkali metal bicarbonate preferably includes potassium bicarbonate and / or sodium bicarbonate; the concentration of the ammonia water is preferably 25-28wt%, and in a specific embodiment, it can be 25wt%, 26wt%, 27wt% or 28wt%. In the present invention, the mass of the alkaline catalyst preferably accounts for 1-5% of the mass of the lignin-furfural mixed solution, and in a specific embodiment, it can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%. Compared with the use of a strong base catalyst, the present invention uses a weakly alkaline or moderately alkaline alkali metal carbonate and / or alkali metal bicarbonate, ammonia water as a catalyst, which can reduce the damage caused by the alkali to the structure of lignin.
[0035] In the present invention, the temperature of the second mixing is 60-80°C, and in a specific embodiment it can be 60°C, 65°C, 70°C, 75°C or 80°C; the time of the second mixing is preferably 20-40min, and in a specific embodiment it can be 20min, 25min, 30min, 35min or 40min; the mixing under the above conditions of the present invention can fully and uniformly mix lignin, furfural and alkaline catalyst.
[0036] In the present invention, the temperature of the addition-polycondensation reaction is preferably 80-120°C, and in specific embodiments it can be 80°C, 90°C, 100°C, 110°C or 120°C; the time of the addition-polycondensation reaction is preferably 1-3h, and in specific embodiments it can be 1h, 1.5h, 2h, 2.5h or 3h; the addition-polycondensation reaction is preferably carried out under stirring conditions.
[0037] The present invention adopts the lignin-furfural mixed solution as the raw material for preparing phenolic resin. The bonding strength of the prepared lignin-furfural biomass-based phenolic resin is higher than that of the lignin-furfural biomass-based phenolic resin prepared by dissolving lignin with a non-acetone solvent. The bonding strength of the lignin-furfural biomass-based phenolic resin at room temperature reaches 4.2±0.3MPa, and the adhesive performance is much higher than the national standard (≥0.7MPa, GB / T14732-2017). In the dry bonding strength test of the lignin-furfural biomass-based phenolic resin prepared by the present invention, all wood samples bonded with the lignin-furfural biomass-based phenolic resin showed 100% wood damage and good adhesive strength. Moreover, the lignin-furfural mixed solution prepared by the present invention can completely replace phenol and formaldehyde raw materials, has the characteristics of being green, non-toxic and environmentally friendly, and can greatly alleviate the pressure of oil resource shortage.
[0038] The present invention also provides the use of the lignin-furfural biomass-based phenolic resin described in the above technical solution as an adhesive, wear-resistant material, waterproof material or insulating material. In the present invention, the adhesive preferably includes an adhesive for wood. In the present invention, the lignin-furfural biomass-based phenolic resin is preferably used in the furniture board processing industry or the construction industry. The lignin-furfural biomass-based phenolic resin provided by the present invention has high bonding strength at room temperature, which meets the national standard bonding strength requirement of phenolic resin wood adhesive ≥0.7MPa (GB / T14732-2017), and has good application prospects as an adhesive.
[0039] The present invention also provides a plywood, wherein the adhesive used includes the lignin-furfural biomass-based phenolic resin described in the above technical solution.
[0040] The present invention also provides a method for preparing the plywood described in the above technical solution, comprising the following steps: applying adhesive to the slabs, laminating and hot pressing to obtain the plywood; the adhesive comprises the lignin-furfural biomass-based phenolic resin described in the above technical solution.
[0041] In the present invention, the thickness of the slab is preferably 0.4-1 mm, and in a specific embodiment, it can be 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm. In the present invention, the material of the slab preferably includes hardwood, softwood or a composite material; the hardwood preferably includes oak or walnut; the softwood preferably includes pine or fir. The present invention has no special limitation on the material of the composite material, and a composite material well known to those skilled in the art can be used.
[0042] In the present invention, the number of layers of the slab in the plywood is preferably 3 to 13 layers, and in specific embodiments can be 3 layers, 5 layers, 7 layers, 9 layers, 11 layers or 13 layers; the wood grain directions of each layer of veneer are arranged perpendicularly to each other to increase the stability of the plywood.
[0043] In the present invention, the amount of adhesive applied is preferably 150-250 g / m 2 In a specific embodiment, it can be 150g / m 2 , 170g / m 2 , 190g / m 2 , 210g / m 2 , 230g / m 2 or 250g / m 2 .
[0044] In the present invention, the temperature of the hot pressing is preferably 120-180°C, and in specific embodiments, it can be 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C; the pressure of the hot pressing is preferably 1-1.5 MPa, and in specific embodiments, it can be 1 MPa, 1.1 MPa, 1.2 MPa, 1.3 MPa, 1.4 MPa or 1.5 MPa; the time of the hot pressing is preferably 3-6 min, and in specific embodiments, it can be 3 min, 4 min, 5 min or 6 min.
[0045] After the hot pressing is completed, the present invention preferably further comprises cooling to room temperature after placing to obtain a plywood. In the present invention, the placing time is preferably 30 to 60 minutes, and in a specific embodiment, it can be 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes. The present invention has no special limitation on the cooling, and cooling to room temperature is sufficient.
[0046] The plywood prepared by the present invention can meet the requirements of GB / T 9846-2015 (Class I board: ≥0.70MPa), and because it uses all-biomass-based raw materials, it does not contain toxic substances such as formaldehyde. It has huge market potential as a furniture processing board in indoor, school, hospital and other scenes.
[0047] In order to further illustrate the present invention, the lignin-furfural biomass-based phenolic resin provided by the present invention and its preparation method and application are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0048] Example 1 The dried and crushed corn cobs were sieved through a 40-60 mesh sieve to obtain corn cob materials. 100 g of corn cob materials were added to a high-pressure reactor, and acetone-water mixed solvent (water volume fraction was 20%) and sulfuric acid were added to obtain an acidic mixed solution; the content of corn cob materials in the acidic mixed solution was 10 wt%, and the content of sulfuric acid was 5 wt%. After the reactor was closed, nitrogen was introduced to a pressure of 1.5-1.6 MPa. The temperature control system and the heat transfer oil circulation system of the reaction device were turned on to heat the high-pressure reactor. When the temperature was heated to 160 ° C, the timing was started, the reaction lasted for 5 minutes, the heating was stopped and the materials were released, and solid-liquid separation was performed to obtain solid acid residue (high-purity cellulose) and liquid components respectively. Sodium carbonate was added to the liquid component to neutralize sulfuric acid to pH = 7, and solid-liquid separation was performed. The obtained liquid component was subjected to reduced pressure distillation to recover acetone to obtain a lignin-furfural mixed solution (lignin 12.95 g, furfural 10.9 g, lignin is lignin soluble in acetone).
[0049] Anhydrous potassium carbonate (accounting for 3% of the mass of the lignin-furfural mixed solution) was added to the lignin-furfural mixed solution, stirred at 60°C for 20 minutes, heated to 110°C and stirred for reaction for 2 hours to obtain a lignin-furfural biomass-based phenolic resin.
[0050] The oak veneer with a thickness of 0.5 mm was coated with lignin-furfural biomass-based phenolic resin (the amount of glue applied was 150 g / m 2 ), arranged vertically and staggered in the direction of wood grain, stacked 9 layers, hot pressed for 3 minutes at 120℃ and 1.1MPa, left for 30 minutes and cooled to room temperature to obtain plywood. According to GB / T 9846-2015, the plywood was tested, and the results showed that the bonding strength of the plywood was 3.90MPa and the wood destruction rate was 100%, indicating that the bonding strength of the lignin-furfural biomass-based phenolic resin was good.
[0051] Example 2 The dried and crushed bamboo powder was sieved through a 20-40 mesh sieve to obtain a bamboo powder material. 100 g of bamboo powder material was added to a high-pressure reactor, and an acetone-water mixed solvent (water volume fraction was 25%) and sulfuric acid were added to obtain an acidic mixed solution; the content of bamboo powder material in the acidic mixed solution was 10 wt%, and the content of sulfuric acid was 5 wt%. After the reactor was closed, nitrogen was introduced to a pressure of 1.5-1.6 MPa. The temperature control system and the heat transfer oil circulation system of the reaction device were turned on to heat the high-pressure reactor. When it was heated to 160 ° C, the timing was started, the reaction lasted for 5 minutes, the heating was stopped and the material was released, and solid-liquid separation was performed to obtain solid acid residue (high-purity cellulose) and liquid components respectively. Potassium carbonate was added to the liquid component to neutralize sulfuric acid to pH = 7, and solid-liquid separation was performed. The obtained liquid component was subjected to reduced pressure distillation to recover acetone to obtain a lignin-furfural mixed solution (lignin 19.6 g, furfural 4.8 g, lignin is lignin soluble in acetone).
[0052] 11 g of furfural was added to the lignin-furfural mixed solution, and anhydrous potassium carbonate (accounting for 4% of the mass of the lignin-furfural mixed solution) was added, and the mixture was stirred at 70° C. for 35 min, and the mixture was heated to 110° C. and stirred for 3 h to obtain a lignin-furfural biomass-based phenolic resin.
[0053] The oak veneer with a thickness of 0.7 mm was coated with lignin-furfural biomass-based phenolic resin (the amount of glue applied was 160 g / m 2 ), arranged vertically and staggered in the direction of wood grain, stacked 5 layers, hot pressed for 3.5 minutes at 130℃ and 1.2MPa, left for 40 minutes and cooled to room temperature to obtain plywood. According to GB / T 9846-2015, the plywood was tested, and the results showed that the bonding strength of the plywood was 3.50MPa and the wood destruction rate was 100%.
[0054] Example 3 The dried and crushed corn stalks were sieved through a 30-60 mesh sieve to obtain corn stalk materials. 100 g of corn stalk materials were added to a high-pressure reactor, and acetone-water mixed solvent (water volume fraction of 30%) and phosphoric acid were added to obtain an acidic mixed solution; the content of corn stalk materials in the acidic mixed solution was 20 wt%, and the content of phosphoric acid was 10 wt%. After the reactor was closed, nitrogen was introduced to a pressure of 1.5-1.6 MPa. The temperature control system and the heat transfer oil circulation system of the reaction device were turned on to heat the high-pressure reactor. When the temperature was heated to 160 ° C, the timing was started, the reaction lasted for 5 minutes, the heating was stopped and the materials were released, and solid-liquid separation was performed to obtain solid acid residues (high-purity cellulose) and liquid components, respectively. Calcium carbonate was added to the liquid component to neutralize phosphoric acid to pH = 7, solid-liquid separation was performed, and the obtained liquid component was subjected to reduced pressure distillation to recover acetone to obtain a lignin-furfural mixed solution (7 g lignin, 8.15 g furfural, lignin is lignin soluble in acetone).
[0055] Add 3.8 g of lignin to the lignin-furfural mixed solution, add anhydrous potassium bicarbonate (accounting for 2% of the mass of the lignin-furfural mixed solution), stir at 70°C for 25 minutes, heat to 105°C and stir for 1 hour to obtain lignin-furfural biomass-based phenolic resin.
[0056] The pine veneer with a thickness of 0.5 mm was coated with lignin-furfural biomass-based phenolic resin (the amount of glue applied was 170 g / m 2 ), arranged vertically and staggered in the direction of wood grain, stacked 7 layers, hot pressed for 3 minutes at 120℃ and 1.3MPa, left for 30 minutes and cooled to room temperature to obtain plywood. According to GB / T 9846-2015, the plywood was tested, and the results showed that the bonding strength of the plywood was 3.65MPa and the wood destruction rate was 100%.
[0057] Example 4 The dried and crushed bagasse was sieved through a 40-60 mesh sieve to obtain bagasse material. 100g of bagasse material was added to a high-pressure reactor, and an acetone-water mixed solvent (water volume fraction of 30%) and phosphoric acid were added to obtain an acidic mixed solution; the content of bagasse material in the acidic mixed solution was 20wt%, and the content of phosphoric acid was 10wt%. After the reactor was closed, nitrogen was introduced to a pressure of 1.5-1.6MPa. The temperature control system and the heat transfer oil circulation system of the reaction device were turned on to heat the high-pressure reactor. When it was heated to 160°C, the timing was started, the reaction lasted for 5 minutes, the heating was stopped and the material was released, and solid-liquid separation was performed to obtain solid acid residue (high-purity cellulose) and liquid components respectively. Ammonia water was added to the liquid component to neutralize sulfuric acid to pH=7, and solid-liquid separation was performed. The obtained liquid component was subjected to reduced pressure distillation to recover acetone to obtain a lignin-furfural mixed solution (14g lignin, 7.85g furfural, lignin is lignin soluble in acetone).
[0058] Add 3.4 g of furfural to the lignin-furfural mixed solution, add ammonia water (accounting for 3% of the mass of the lignin-furfural mixed solution), stir at 75°C for 25 minutes, heat to 115°C and stir to react for 2.5 hours to obtain lignin-furfural biomass-based phenolic resin.
[0059] The oak veneer with a thickness of 1 mm was applied with lignin-furfural biomass-based phenolic resin (the amount of glue was 180 g / m 2 ), arranged vertically and staggered in the direction of wood grain, stacked 7 layers, hot pressed for 3 minutes at 120℃ and 1.4MPa, left for 30 minutes and cooled to room temperature to obtain plywood. According to GB / T 9846-2015, the plywood was tested, and the results showed that the bonding strength of the plywood was 3.80MPa and the wood destruction rate was 100%.
[0060] Example 5 The dried and crushed wheat straw was passed through a 40-60 mesh sieve to obtain wheat straw material. 100g of wheat straw material was added to a high-pressure reactor, and an acetone-water mixed solvent (water volume fraction of 30%) and phosphoric acid were added to obtain an acidic mixed solution; the content of wheat straw material in the acidic mixed solution was 25wt%, and the content of phosphoric acid was 20wt%. After the reactor was closed, nitrogen was introduced to a pressure of 1.5-1.6MPa. The temperature control system and the heat transfer oil circulation system of the reaction device were turned on to heat the high-pressure reactor. When it was heated to 160°C, the timing was started, the reaction lasted for 5min, the heating was stopped and the material was released, and solid-liquid separation was performed to obtain solid acid residue (high-purity cellulose) and liquid components respectively. Ammonia water was added to the liquid component to neutralize sulfuric acid to pH=7, and solid-liquid separation was performed. The obtained liquid component was subjected to reduced pressure distillation to recover acetone to obtain a lignin-furfural mixed solution (lignin 6.4g, furfural 7.85g, lignin is lignin soluble in acetone).
[0061] 5.6 g of lignin was added to the lignin-furfural mixed solution, and anhydrous sodium carbonate (accounting for 1% of the mass of the lignin-furfural mixed solution) was added, and the mixture was stirred at 80° C. for 35 min, and the mixture was heated to 120° C. and stirred for 3 h to obtain a lignin-furfural biomass-based phenolic resin.
[0062] The 0.9 mm thick fir veneer was coated with lignin-furfural biomass-based phenolic resin (the amount of glue applied was 200 g / m 2 ), arranged vertically and staggered in the direction of wood grain, stacked 13 layers, hot pressed for 3 minutes at 150℃ and 1.1MPa, left for 30 minutes and cooled to room temperature to obtain plywood. According to GB / T 9846-2015, the plywood was tested, and the results showed that the bonding strength of the plywood was 3.95MPa and the wood destruction rate was 100%.
[0063] The test results of the hydroxyl content of the lignin component in the lignin-furfural mixed solution prepared in Example 3 are shown in Table 1.
[0064] Table 1 Phenolic hydroxyl content of lignin components in lignin-furfural mixed solution
[0065] As shown in Table 1, the yields of acetone soluble lignin and acetone insoluble lignin are approximately 70% and 30%, respectively. 31 P nuclear magnetic resonance (NMR) analysis showed that the total phenolic hydroxyl content in the acetone soluble fraction (3.82 mmol / g) was higher than that in the acetone insoluble fraction (1.88 mmol / g).
[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a lignin-furfural biomass-based phenolic resin, comprising the following steps: The biomass raw material, the organic solvent-water mixed solvent and the inorganic acid are mixed, the obtained acidic mixed solution is heat-treated under a protective atmosphere, the solid-liquid separation is performed, and the pH value of the obtained liquid component is adjusted to neutral to obtain a lignin-furfural mixed solution; the organic solvent in the organic solvent-water mixed solvent includes acetone; The lignin-furfural mixed solution and an alkaline catalyst are mixed, and the obtained lignin-furfural-catalyst mixed solution is subjected to an addition-polycondensation reaction to obtain a lignin-furfural biomass-based phenolic resin.
2. The preparation method according to claim 1, characterized in that: The biomass raw materials include agricultural and forestry waste biomass and / or energy herbs; The inorganic acid includes sulfuric acid and / or phosphoric acid; The content of biomass raw materials in the acidic mixed liquid is 5-30wt%, and the content of inorganic acid is 1-50wt%; The volume fraction of water in the organic solvent-water mixed solvent is 10-50%.
3. The preparation method according to claim 1 or 2, characterized in that: The heat treatment temperature is 140-180° C., the heat preservation time is 5-10 min, and the pressure is 0.1-2 MPa.
4. The preparation method according to claim 1, characterized in that: The mass ratio of lignin to furfural in the lignin-furfural-catalyst mixed solution is 0.8-1:0.6-0.8; when the mass ratio of lignin to furfural does not meet 0.8-1:0.6-0.8, additional lignin or furfural is added.
5. The preparation method according to claim 1, characterized in that: The alkaline catalyst includes one or more of alkali metal carbonate, alkali metal bicarbonate and ammonia; The mass of the alkaline catalyst accounts for 1-5% of the mass of the lignin-furfural mixed solution.
6. The preparation method according to claim 1, 4 or 5, characterized in that: The condensation reaction temperature is 80-120° C. and the reaction time is 1-3 hours.
7. The lignin-furfural biomass-based phenolic resin obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the lignin-furfural biomass-based phenolic resin according to claim 7 as an adhesive, wear-resistant material, waterproof material or insulating material.
9. A plywood, characterized in that: The adhesive used includes the lignin-furfural biomass-based phenolic resin described in claim 7.
10. The method for preparing plywood according to claim 9, characterized in that: The following steps are involved: The slabs are applied with adhesive, laminated, and hot-pressed to obtain the plywood.
Citation Information
Patent Citations
Method for co-producing furaldehyde, cellulose and lignin by depolymerizing biomasses
CN108530404A
Method for extracting lignin as adhesive from wood biomass
CN114736652A
Thermosetting lignin-containing resin
GB948776A
Phenol-free impregnation resin
WO2018193166A1
Method for extracting lignin from woody biomass and using lignin as adhesive
WO2023208015A1